Analysis Of The Application Of Franchising Systems In Street Food Businesses To Improve The Competitiveness Of Msmes - Ariyanto, Beny; Sudarmiatin; Puji Handayati; Naswan Suharsono (International journal of technology and education research, 2025)
This study aims to analyze the application of franchising systems in street food businesses and their impact on improving the competitiveness of MSMEs. Culinary MSMEs, especially in the street food sector, have high growth potential but face various challenges such as weak branding, inconsistent product quality, and limited managerial capacity. The franchising and micro-franchising models have emerged as potential strategies to overcome these challenges through operational standardization, management support, and brand strength. This study uses a qualitative approach with a case study method through in-depth interviews and observations of street food business actors who are franchisees. The results show that the implementation of SOPs, training, and supervision from the franchisor improve operational efficiency, product consistency, brand identity, and consumer trust. In addition, franchising has been proven to expand market access, increase sales, and help street food businesses move upmarket. However, the study also found challenges such as limited innovation, dependence on the franchisor for raw materials, and the burden of royalty fees. Overall, the franchising system has proven to be an effective strategy for increasing the competitiveness of MSMEs in the street food sector through a combination of standardization, brand strengthening, and ongoing management support.